The Effect of the PesantrenKU Application on Santri Independence in Online Learning - Agung Zulfikri (Westscience Press, 2024)
This study investigates the effect of the PesantrenKU application on the independence of santri (students) in online learning within Indonesia. Utilizing a quantitative analysis approach, data was collected from 100 santri using structured questionnaires. The collected data was then analyzed using SPSS version 25. The findings indicate that the use of the PesantrenKU application significantly enhances santri independence in their online learning activities. The results show significant positive relationships between PesantrenKU application usage and three dimensions of learning independence: self-regulation, self-motivation, and self-directed learning. These results suggest that integrating digital tools like PesantrenKU can play a crucial role in promoting independent learning in Islamic boarding schools, ultimately contributing to broader educational objectives in the region.